Shorter CAG repeat in the AR gene is associated with atypical hyperplasia and breast carcinoma - Abreu, Francine Blumental de [UNESP]; Pirolo Júnior, Leandro; Canevari, Renata de Azevedo [UNESP]; Rosa, Fabíola Encinas [UNESP]; Moraes Neto, Francisco Alves; Caldeira, José Roberto Fígaro; Rainho, Claudia Aparecida [UNESP]; Rogatto, Silvia Regina [UNESP] (My University, 2007)
Background: Previous reports into the role of [CAG]n repeat lengths in the androgen receptor (AR) gene indicate that these may play an important part in the development and progression of breast cancer, however, knowledge regarding benign breast lesions is limited. Patients and Methods: PCR-based GeneScan analysis was used to investigate the [CAG]n repeat length at exon 1 of the AR gene in 59 benign breast lesions (27 fibroadenomas, 18 atypical hyperplasias, and 14 hyperplasias without atypia) and 54 ductal breast carcinomas. Seventy-two cancer-free women were used as a control group. In addition, [CAG]n repeats were evaluated for the presence of loss of heterozygosity (LOH) and microsatellite instability (MSI) in a subset of these samples (27 fibroadenomas, 14 hyperplasias without atypia and 22 breast carcinomas). Results: Shorter [CAG]n repeat lengths were strongly correlated with atypical hyperplasias (p=0.0209) and carcinomas (p<0.0001). LOH was found in 1/12 and 4/20 informative cases of hyperplasias without atypia and breast carcinomas, respectively. Three patients with breast carcinoma who had previously presented atypical hyperplasia showed a reduction in the [CAG]n repeat length in their carcinomas. Conclusion: Short [CAG]n repeat length (≤20) polymorphisms are strongly associated with breast carcinomas and atypical hyperplasias. Although non-significant, a subgroup of patients with breast carcinoma and genotype SS showed an association with parameters of worse outcome.
Keywords: [CAG] n repeats; Androgen receptor gene; Breast carcinoma; Fibroadenoma; Hyperplasia; androgen receptor; adolescent; adult; aged; breast carcinoma; breast hyperplasia; controlled study; female; genetic analysis; heterozygosity loss; human; human tissue; major clinical study; microsatellite instability; nucleotide repeat; priority journal; Adolescent; Adult; Aged; Aged, 80 and over; Alleles; Breast; Breast Neoplasms; Carcinoma, Ductal, Breast; Female; Humans; Middle Aged; Polymerase Chain Reaction; Polymorphism, Genetic; Receptors, Androgen; Trinucleotide Repeats